Ventilatory response during exercise among chronic Chagas cardiopathy patients - Oliveira, Fátima Palha de; Pedrosa, Roberto Coury (São Paulo Medical Journal, 2006)
CONTEXT AND OBJECTIVE: The change in slope of the V. E/V CO2 curve with time during exercise (V E/V CO2 slope) has been recommended as a parameter for analyzing the ventilatory response during exercise among patients with heart failure of different etiologies. The aim of this work was to evaluate the ventilatory response among patients with chronic Chagas cardiopathy. METHODS: Forty-eight patients, divided into four groups according to the Los Andes clinical/hemo- dynamic classification, were studied. They were also cla. ssified according to peak oxygen uptake (peak V O2) for a second analysis. The results from the patients were compared with results from a con- trol group consisting of 21 healthy male volunteers (no Chagas disease). Exercise was performed on a cycle ergometer with loads increasing at the rate of 12.5 watts/min, and exercise duration was symptom-limited. Gas concentration and flow rate data were fed into a computer, which produced a real-time report on ventilatory and gas exchange parameters (breath-by-breath). The ventilatory parameters of V E/V CO2 slope and V E/V CO2 ratio computed at different times of the test were adopted. RESULTS: Although there were no significant differences in V E/V CO2 ratio and V E/V CO2 slope when patients were grouped using the Los Andes clinical/hemodynamic classification, these parameters varied significantly when peak V O2 was used to define patient groups. CONCLUSION: Our results indicate that progres- sive deterioration in ventilatory response among chronic Chagas cardiopathy patients during exer- cise is m. ore evident when the functional capacity (peak V O2) is reduced, than when changes are related to the Los Andes classification.